Test rig development and TEG characterisation for high efficient thermoelectric power conversion system - Vinh An, Tran Khanh (2015)
In order to improve the attractiveness of thermoelectric power generation, besides improving efficiency of thermoelectric materials, improvements on power conversion system are strongly required. To allow for better design of an interface between thermoelectric generator and load, a test rig for TEGs is required. Since most of the current TEG test rigs present are either too complicated, or too simplistic without much upgradability, this project focus on developing a simple, small and compact yet capable test rig. The test rig developed is able to allow operator to test characteristics of different TEG easily and consistently while also serving as a testing platform for testing of multiple TEGs, thus enables future DC-DC converters’ performance to be studied and optimised.